2021
DOI: 10.1002/ajcp.12510
|View full text |Cite
|
Sign up to set email alerts
|

Peer‐based interventions targeting suicide prevention: A scoping review

Abstract: Peers of individuals at risk for suicide may be able to play important roles in suicide prevention. The aim of the current study is to conduct a scoping review to characterize the breadth of peer‐delivered suicide prevention services and their outcomes to inform future service delivery and research. Articles were selected based on search terms related to peers, suicide, or crisis. After reviews of identified abstracts (N = 2681), selected full‐text articles (N = 286), and additional references (N = 62), a tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 134 publications
(222 reference statements)
0
24
0
Order By: Relevance
“…Three reviews were found that addressed peer-led interventions. One scoping review focused on peer support programs (excluding bereavement programs) that aim to reduce suicidality in people deemed at risk [ 21 ], and another scoping review focusing on describing the breadth of peer-delivered suicide preventions services and their outcomes, to inform future service delivery and research [ 22 ]. Bartone et al’s [ 19 ] systematic review focused on peer support services for bereaved survivors, irrespective of the cause of death.…”
Section: Introductionmentioning
confidence: 99%
“…Three reviews were found that addressed peer-led interventions. One scoping review focused on peer support programs (excluding bereavement programs) that aim to reduce suicidality in people deemed at risk [ 21 ], and another scoping review focusing on describing the breadth of peer-delivered suicide preventions services and their outcomes, to inform future service delivery and research [ 22 ]. Bartone et al’s [ 19 ] systematic review focused on peer support services for bereaved survivors, irrespective of the cause of death.…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to previous reviews on mental conditions, as they mainly addressed suicide prevention and dementia. Bowersox et al [169] conducted a scoping review on the function of peers in the prevention of suicidal behaviors. The authors concluded that peer-based interventions could play an important role in suicide prevention.…”
Section: Our Results In the Context Of Previous Researchmentioning
confidence: 99%
“…Existing guidelines for the training and support of mental health LEW [ 12 ] lack tailored components deemed essential to the training and support of the suicide prevention LEW, such as their ability to discuss suicide safely without increasing suicide risk or stigma, as well as their own safety in terms of suicide risk [ 13 ]. Furthermore, the skills required by the suicide prevention LEW for supporting those in suicidal distress through to those bereaved by suicide demand a nuanced understanding of impacts of suicide-related stigma and the shame, guilt, and other internalised negative experiences associated with suicide lived experience [ 14 , 15 ]. Specialised skills relevant to suicide prevention are acknowledged in the National Lived Experience (Peer) Workforce Development Guidelines as being challenging to implement [ 6 ].…”
Section: Introductionmentioning
confidence: 99%